Advantages of OKID-ERA Identification in Control Systems. An Application to the Tennessee Eastman Plant - Yapur, Sergio Federico (2022)
Data-driven OKID-ERA identification of the open-loop Tennessee Eastman plantis performed to obtain a linear model for control design purposes. Analysissuch as numerical conditioning, output response errors, and zero-pole mappingshighlight some definite advantages of the OKID-ERA approach when compared withmodels derived from typical linearization techniques. The plant under study isa recognized benchmark in the field of plant-wide control systems.